Nilai-Nilai Pendidikan Multikultural Dalam Pendidikan Agama Hindu Menurut Kitab Niti Sataka - Palguna Utama, I Putu Shandy; Sawitri, Ida Ayu Kade (Jayapangus Press, 2023)
Multicultural education responds to ethnic, social, and cultural conflicts with a focus on values ​​of mutual respect, sincerity, and tolerance. In Indonesia, which is rich in diversity, challenges such as corruption and violence threaten social harmony. Religious education often exacerbates conflicts with its exclusive approach, when it should strengthen universal morality and inclusive understanding. Multicultural education in educational institutions should instill values ​​of peace and pluralism so that students understand and appreciate religious diversity. This research uses qualitative methods with literature studies to understand the values ​​of multicultural education in Hinduism, especially in the Niti Sataka scripture. Sociological and anthropological approaches are used to analyze individual interactions in the context of religion and culture, as well as social practices in the holistic context of human culture. Multicultural education integrates diverse cultures and values ​​to create equality in education and appreciate ethnic diversity. The goal of multicultural education in Indonesia is to develop awareness of cultural diversity and strengthen positive attitudes towards diversity, with Hindu religious education emphasizing caring values ​​aligned with multicultural education. The Niti Sataka scripture highlights awareness of ignorance, wisdom, and other values ​​that support peaceful living. Multicultural education aims to acknowledge student diversity, promote positive attitudes towards differences, and assist in the development of social skills and cross-cultural understanding.